Novel green nano composites films fabricated by indigenously synthesized graphene oxide and chitosan. (1st August 2016) - Khan, Younus H.; Islam, Atif; Sarwar, Afsheen; Gull, Nafisa; Khan, Shahzad M.; Munawar, Muhammad A.; Zia, Saba; Sabir, Aneela; Shafiq, Muhammad; Jamil, Tahir
Highlights: Chitosan-GO composite films fabricated by solution casting technique. FTIR studies confirmed the homogenous blending of chitosan and GO. Higher Mw chitosan composite (GOCC-1000) showed the best mechanical strength. Thermal stability of GOCC-1000 enhanced as residual content increased up to 56%. SEM analysis of composites sheets showed excellent dispersion of GO with chitosan. Abstract: Graphene oxide (GO) was indigenously synthesized from graphite using standard Hummers method. Chitosan-graphene oxide green composite films were fabricated by mixing aqueous solution of chitosan and GO using dilute acetic acid as a solvent for chitosan. Chitosan of different viscosity and calculated molecular weight was used keeping amount of GO constant in each composite film. The structural properties, thermal stability and mechanical properties of the composite films were investigated using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and tensile test. FTIR studies revealed the successful synthesis of GO from graphite powder and it was confirmed that homogenous blending of chitosan and GO was promising due to oxygenated functional groups on the surface of GO. XRD indicated effective conversion of graphite to GO as its strong peak observed at 11.06° as compared to pristine graphite which appeared at 26°. Moreover, mechanical analysis confirmed the effect of molecular weight on the mechanical properties of chitosan-GO composites showing that higher molecular weight chitosan composite (GOCC-1000) showed best strength (higher than 3 GPa) compared to other composite films. Thermal stability of GOCC-1000 was enhanced for which residual content increased up to 56% as compared to the thermal stability of GOCC-200 whose residue was restricted to only 24%. The morphological analysis of the composites sheets by SEM was smooth having dense structure and showed excellent interaction, miscibility, compatibility and dispersion of GO with chitosan. The prepared composite films find their applications as biomaterials in different biomedical fields.